2021
DOI: 10.3390/ijms22147606
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Influences of Cystic Fibrosis Transmembrane Conductance Regulator Drugs on Lung Inflammation in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is caused by a defect in the cystic fibrosis transmembrane conductance regulator protein (CFTR) which instigates a myriad of respiratory complications including increased vulnerability to lung infections and lung inflammation. The extensive influx of pro-inflammatory cells and production of mediators into the CF lung leading to lung tissue damage and increased susceptibility to microbial infections, creates a highly inflammatory environment. The CF inflammation is particularly driven by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
(126 reference statements)
0
14
0
1
Order By: Relevance
“…In normal homeostatic conditions, neutrophils are short-lived and undergo spontaneous apoptosis to guarantee the termination of the inflammatory insult but, similarly to macrophages, are also characterized by remarkable plasticity. Indeed, although when they leave the bone marrow neutrophils have already a default pro-apoptotic program, it can be modified by stimuli received in the target tissue including IL-8 and GM-CSF, that promote their persistence and longevity [ 71 , 74 , 75 ]. IL-8, also known as CXCL8, is mainly produced by AECs and macrophages, and one of its major functions is to attract and activate neutrophils and delay their apoptosis via their IL-8 receptor (mainly CXCR2) [ 76 , 77 ].…”
Section: The Role Of Cftr Dysfunction In Phagocyte...mentioning
confidence: 99%
“…In normal homeostatic conditions, neutrophils are short-lived and undergo spontaneous apoptosis to guarantee the termination of the inflammatory insult but, similarly to macrophages, are also characterized by remarkable plasticity. Indeed, although when they leave the bone marrow neutrophils have already a default pro-apoptotic program, it can be modified by stimuli received in the target tissue including IL-8 and GM-CSF, that promote their persistence and longevity [ 71 , 74 , 75 ]. IL-8, also known as CXCL8, is mainly produced by AECs and macrophages, and one of its major functions is to attract and activate neutrophils and delay their apoptosis via their IL-8 receptor (mainly CXCR2) [ 76 , 77 ].…”
Section: The Role Of Cftr Dysfunction In Phagocyte...mentioning
confidence: 99%
“…However, none of the studies described looked at the influence of CFTR modulators upon alveolar macrophage surface receptors or phagocytic signaling pathways. Other studies examined the influence of CFTR modulators on inflammatory signaling in monocytes and macrophages and were reviewed elsewhere [ 181 , 182 ].…”
Section: Cftr Modulators/other Therapeutics and Cf Phagocytosismentioning
confidence: 99%
“…Some studies have suggested that CFTR modulators may also decrease the inflammatory response in CF airways, an effect that would further contribute to improved disease outcomes [ 57 ]; however, to date conflicting results have been reported and data still remain inconclusive (reviewed in [ 58 , 59 ]). Furthermore, it remains to be defined whether these drugs are capable of restoring dysfunctional CFTR in immune cells that may contribute to the exaggerated inflammatory process and the impaired clearance of pathogens in CF airways [ 60 , 61 ].…”
Section: Airway Infections In Cystic Fibrosismentioning
confidence: 99%